Pemikiran Muhammad Husain Haikal tentang pemerintahan Islam - Muhammad; Namira; Sabina; Savira; Rasyid (Tabayyun : Journal Of Islamic Studies, 2024)
The aim of this study is to describe Muhammad Husain Haikal's thoughts about Islamic government. In this research the researcher used Using a qualitative methodology, this kind of study employed descriptive research, namely focusing on actual problems. Research findings show that Muhammad Husain Haikal was an Egyptian intellectual and writer whose progressive and reformist views on Islamic governance reflected an attempt to bridge Islamic tradition with the demands of modernity. Haikal believes that Islamic governments must adopt reforms to face the challenges of the times, with a contextual and dynamic interpretation of sharia. He supports the concept of separation of powers to achieve justice and believes that democratic principles do not conflict with Islam, encouraging public participation in governance. Social justice is the main pillar in his view, where the government must ensure a fair distribution of wealth. Haikal also does not reject Western influence as a whole, but suggests its selective adoption in accordance with Islamic values. The role of ulama is recognized as important, but they must be progressive and open to change. Haikal's thinking emphasizes adaptation and modernization within the framework of Islamic principles to create a just and effective government.